Hell and Night - Costantino, Thea (Lawrence Wilson Art Gallery, 2016)
Hell and Night is a short film that considers the character of Iago, the villain of Shakespeare’s Othello. While the motivations for Iago’s destructive machinations are never made entirely clear in the play, his narcissism, exaggerated sense of personal injury and contempt for those around him are traits that are easily translated into a contemporary context. The film draws on his lines: “Hell and night | Will bring this monstrous birth to the world’s light,” and “Knavery’s plain face is never seen till us’d”. Anthony DiMatteo explores Shakespeare’s references to mythology in constructing Iago’s revenge plot as a ‘monstrous birth’. He reads the line as an allusion to Cerberus, one of the labours of Hercules, “the only hellish inhabitant literally brought to the world’s light” (333), which brings the play’s repeated references to dogs into further context Building on interpretations of Iago as a demonic character, his monstrous transformation is prefigured by a sinister act involving a dog, which ultimately leads to the revelation of ‘knavery’s plain face’. This short film was commissioned by the University of Western Australia and The Lawrence Wilson Art Gallery to respond to the 400th anniversary of Shakespeare’s death and to reflect on the relevance of his work in the present day. The work has since been acquired by the University for its art collection.